Enhancing Aquaculture Efficiency through IoT-Based Monitoring of Solar PV Systems - Handoko, Catur Rakhmad; Sutrisno, Imam; Sidi, Pranowo; Ardiansyah (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research presents the design and implementation of an IoT-based monitoring system for solar photovoltaic (PV) performance in shrimp aquaculture ponds. The system aims to optimize the use of solar energy for powering critical operations such as water pumps and aerators in off-grid environments. It integrates sensors, a microcontroller, and cloud-based data visualization to track parameters including panel voltage, current, temperature, and power output. A prototype was deployed in a shrimp farm over a two-week period, with continuous data logging and real-time monitoring. The results indicate improved energy management and system reliability, supporting operational efficiency and sustainability in aquaculture. This study contributes to smart aquaculture practices by introducing a scalable and low-cost renewable energy monitoring solution